2007
DOI: 10.1017/s0022215107000631
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of oropharyngeal mucosal plasmacytosis related to toothpaste

Abstract: Mucosal plasmacytosis is a benign inflammatory process that may appear to be more sinister on clinical examination. Skin patch testing is a useful adjunct in confirming the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
3
0
1
Order By: Relevance
“…Numerous reports have made suggestions as to possible causes. A case presented by Tong et al believed that a toothpaste may be responsible, with the possibility of an ingredient evoking a hypersensitivity reaction. Other case reports have emphasized the presence of severe periodontitis .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have made suggestions as to possible causes. A case presented by Tong et al believed that a toothpaste may be responsible, with the possibility of an ingredient evoking a hypersensitivity reaction. Other case reports have emphasized the presence of severe periodontitis .…”
Section: Discussionmentioning
confidence: 99%
“…La prevalencia del plasmocitoma intraóseo solitario en cabeza y cuello y particularmente en mandíbula es extremadamente baja de acuerdo a lo reportado en múltiples artículos relacionados con el tema (4)(5)(6)12).…”
Section: Discussionunclassified
“…It is seen that this clinical picture in gingiva was also named as atypical gingivostomatitis, idiopathic gingivostomatitis and allergic gingivostomatitis in previous years (2). It was suggested that it was common with hypersensitivity reactions and defined also as an idiopathic, inflammatory clinical entity (3). This condition was thought to be and allergic reaction to unknown ingredient mouthwash, toothpaste and chewing gum other causes like decreased vitamin intake and local infections was suggested (4).…”
Section: Introductionmentioning
confidence: 99%